Maintenance of cleanliness of the Rizal park - Gonzales, Leticia Ritez 1934- (s.n.], 1971)
The healthful environment of Rizal Park which is in flagrant contrast to its surrounding aroused the writer's interest to find out the reasons behind the park's continued cleanliness. The normative survey which was supplemented by the bibliographical descriptive method of research was utilized in this investigation.